Feeling Richer and Happier? Self-Perceived Economic Welfare and Life Satisfaction: Evidence of 'Easterlin Paradox' from Russian Longitudinal Data - Olivia S. Jin; Phanindra V. Wunnava (Global Labor Organization (GLO), 2020)
Do you feel happier when you think you are richer? How does the perception of your own economic welfare affect your life satisfaction? This study examines subjective economic welfare and life satisfaction using the Russia Longitudinal Monitoring Survey covering years 1994 through 2018. The study shows that those who perceive themselves to be better off are also more satisfied with their lives, even while controlling for income, unemployment and other demographic characteristics. This study aims to provide a possible explanation of the `Easterlin Paradox a phenomenon in which individuals 'happiness increases with income, yet an increase in income of the whole society does not necessarily increase the happiness of all (1974). The results from this study suggests that the way one perceives their own economic welfare is a significant determinant of life satisfaction, and that the subjective economic welfare may be the driver of the `Easterlin paradox.' The study also suggests the importance of studying subjective economic welfare, with possible implications on income inequality. Our findings suggest that a society with high income inequality, in which a small proportion of the population earns a large proportion of society's income, will have lower collective life satisfaction.
Keywords: D60; D63; I31; 330; Easterlin Paradox; life satisfaction; Ordered Probit; self perceived economic welfare; subjective wellbeing; Russian longitudinal data